`y=r/sqrt(r^2+1)`

`y'=r*(-1/2)(r^2+1)^((-1/2)-1) (2r) + 1/sqrt(r^2+1)`

`y'=-r^2(r^2+1)^(-3/2) + 1/sqrt(r^2+1)`

`y'= -r^2/(r^2+1)^(3/2) +1/sqrt(r^2+1)`

`y'= -(r^2/((r^2+1)(sqrt(r^2+1))))+1/sqrt(r^2+1)`

`y' =(-r^2+r^2+1)/((r^2+1)(sqrt(r^2+1)))`

`y'=(1)/((r^2+1)(sqrt(r^2+1)))`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now